Novel approach to computerized breath detection in lung function diagnostics - Horáček, Jaroslav; Koucký, Václav; Hladík, Milan (Computers in biology and medicine, 2018)
BACKGROUND: Breath detection, i.e. its precise delineation in time is a crucial step in lung function data analysis as obtaining any clinically relevant index is based on the proper localization of breath ends. Current threshold or smoothing algorithms suffer from severe inaccuracy in cases of suboptimal data quality. Especially in infants, the precise analysis is of utmost importance. The key objective of our work is to design an algorithm for accurate breath detection in severely distorted data. METHODS: Flow and gas concentration data from multiple breath washout test were the input information. Based on universal physiological characteristics of the respiratory tract we designed an algorithm for breath detection. Its accuracy was tested on severely distorted data from 19 patients with different types of breathing disorders. Its performance was compared to the performance of currently used algorithms and to the breath counts estimated by human experts. RESULTS: The novel algorithm outperformed the threshold algorithms with respect to their accuracy and had similar performance to human experts. It proved to be a highly robust and efficient approach in severely distorted data. This was demonstrated on patients with different pulmonary disorders. CONCLUSION: Our newly proposed algorithm is highly robust and universal. It works accurately even on severely distorted data, where the other tested algorithms failed. It does not require any pre-set thresholds or other patient-specific inputs. Consequently, it may be used with a broad spectrum of patients. It has the potential to replace current approaches to the breath detection in pulmonary function diagnostics.
Keywords: Signal Processing, Computer-Assisted; Tidal breathing; Female; Infant; dítě; předškolní dítě; počítačové zpracování signálu; ženské pohlaví; diagnóza počítačová; Adolescent; lidé; Multiple breath washout test; Algorithms; Medical algorithm design; Male; Lung function testing; kojenec; Child, Preschool; algoritmy; Breath end; Child; Respiratory Function Tests; mužské pohlaví; respirační funkční testy; Diagnosis, Computer-Assisted; mladiství; Automated breath detection; Humans